Village Economic Institutions Partnership: Towards Rural Business Community Sustainability - Effendi, Soelchan; Sukoharsono , Eko Ganis; Purwanti , Lilik (The International Journal of Accounting and Business Society, 2024)
Purpose — This research aims to develop a collaboration model for village-owned enterprises, micro-entrepreneurs, rural-based medium-sized enterprises, and elements of the local village government to encourage rural economic activity. Design/methodology/approach — This study uses ethnographic methods to explore field facts. Researchers participate in village operational activities; this method is known as participatory observation. Researchers conducted in-depth interviews with informants from the village government, elements managing village-owned enterprises, and Small Business Actors. Documentation data sources come from operational reports of Village-Owned Enterprises and Village Profile Documents. Findings — Village Owned Enterprises is a representation of formal rural economic institutions. The economic activities carried out by Village-Owned Enterprises run on their own and still need to include other local economic actors, such as small-scale home industries. Village-owned enterprises operate like private companies and should be managed socially. Practical implications — This paper develops an economy-based community empowerment model involving local potential and elements of village community groups, which is expected to be an alternative step for Village-Owned Enterprises to create economic activities for villagers. Originality/value — The collaboration of the two business forms can encourage the optimization of rural economic activity. The collaboration of village-owned enterprises and village-scale small-scale enterprises in economic activities is a form of social enterprise. The definition of social enterprise in this situation is that Village-Owned Enterprises provide benefits to the socio-economic life of rural communities and make economic contributions to the internal economic interests of this business unit itself.